Impact of the COVID-19 pandemic on emergency healthcare utilization: a cohort study. (20th October 2021) - Chou, YC; Yen, YF; Chu, DC; Hu, HY
Abstract: Background: Emergency department (ED) crowding is a burden on public health, so understanding the characteristics of frequent ED users is a key concern of the healthcare system and policy makers. This study aims to examine the characteristics and healthcare-seeking behaviors in frequent ED users before and during the COVID-19 pandemic. Methods: A retrospective observational study was conducted on ED users aged 18 years and over admitted to Taipei City Hospital in February 2019-January2020 (before pandemic) and February 2020-January2021 (during pandemic) (N = 120, 011). Frequent and ED users were defined as patients with four or more ED visits in a year. Multivariate logistic regression was used to identify the predictors of frequent ED use before and during the COVID-19 pandemic. Results: Monthly emergency department visits were significantly lower during the pandemic (by 10.1-26.8%). Frequent ED patients had shorter lengths of stay in the ED during the pandemic (212.5 vs.233.9 minutes; P < 0.0001). The proportion of ED patients receiving chest CT examination during the pandemic has increased by 0.5-0.6%. After adjusting for sociodemographic factors, triage status, mode of arrival, and copayment exemption, patients with a triage status of level 4-5 (AOR=1.60, 95% CI: 1.13-2.28), diagnosis of pneumonia (AOR=1.85, 95% CI: 1.07-3.17), giddiness (AOR=2.85, 95% CI: 1.82-4.45), dyspnea (AOR=1.85, 95% CI: 1.00-3.39), or chronic kidney disease (AOR=5.05, 95% CI: 2.66-9.59) were more likely to be frequent ED visitors during the pandemic. Conclusions: Since SAR-CoV-2 is highly contagious, it is imperative to educate non-emergent patients to utilize outpatient medical services rather than emergency medical services to reduce the risk of COVID-19 outbreaks at the ED. Key messages: This study found that the utilization of emergent medical services during the COVID-19 pandemic significantly decreased by 10.1%–26.8% compared to before the COVID-19 pandemic. The lengths of stay in frequent ED users during the COVID-19 pandemic were significantly shorter than that in frequent ED users before the COVID-19 pandemic.